Selecting Critical Properties of Terpenes and Terpenoids through Group-Contribution Methods and Equations of State - Martins, Mónia A.R. (2018)
The knowledge of critical properties is fundamental in engineering process calculations for the estimation of thermodynamic properties and phase equilibria. A literature survey shows a large number of methods for predicting critical properties of different classes of compounds, but no previous study is available to evaluate their suitability for terpenes and terpenoids. In this work, the critical properties of terpenes and terpenoids were first estimated using the group-contribution methods of Joback, Constantinou and Gani, and Wilson and Jasperson. These were then used to calculate densities and vapor pressure through the equations of state Peng-Robinson (PR) and Soave-Redlich-Kwong (SRK) and then compared with the experimental values. On other hand, density and vapor pressure experimental data were used to estimate the critical properties directly by the same equations of state (EoSs), allowing a comparison between the two estimation procedures. For this purpose densities for 17 pure terpenes and terpenoids were here measured at atmospheric pressure in the temperature range (278.15 to 368.15) K. Using the first approach, the best combination is the Joback's method with the Peng-Robinson EoS, despite the high relative deviations found for vapor pressure calculations and difficulties to predict density at low temperatures. Following the second approach, the set of critical properties and acentric factors estimated are able to adequately correlate the experimental data. Both equatio ns show a similar capability to correlate the data with SRK EoS presenting a global %ARD of 3.16 and 0.62 for vapor pressure and density, respectively; while the PR EoS presented 3.61 and 0.66, for the same properties, both giving critical properties estimates also closer to those calculated by the Joback method, which is the recommended group-contribution method for this type of compounds.